2017
DOI: 10.1103/physrevd.95.023522
|View full text |Cite
|
Sign up to set email alerts
|

Fine-tuning challenges for the matter bounce scenario

Abstract: A bouncing universe with a long period of contraction during which the average density is pressureless (the same equation of state as matter) as cosmologically observable scales exit the Hubble horizon has been proposed as an explanation for producing a nearly scale-invariant spectrum of adiabatic scalar perturbations. A well-known problem with this scenario is that, unless suppressed, the energy density associated with anisotropy grows faster than that of the pressureless matter, so the matter-like phase is u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…The anisotropy problem could be alleviated by adding an ekpyrotic scalar field to the matter content, and another possibility is instead that stiff contributions to the equation of state from quantum higher-loop corrections to the action of fermion theories with a four-fermion interaction term could generate an ekpyrotic phase [108]. Alternatively, it might be possible to relate the ekpyrotic field to dark matter; this could potentially address the finetuning issues related to the anisotropy problem discussed in [24]. We leave an investigation of these possibilities for future work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anisotropy problem could be alleviated by adding an ekpyrotic scalar field to the matter content, and another possibility is instead that stiff contributions to the equation of state from quantum higher-loop corrections to the action of fermion theories with a four-fermion interaction term could generate an ekpyrotic phase [108]. Alternatively, it might be possible to relate the ekpyrotic field to dark matter; this could potentially address the finetuning issues related to the anisotropy problem discussed in [24]. We leave an investigation of these possibilities for future work.…”
Section: Discussionmentioning
confidence: 99%
“…Another challenge for the matter bounce scenario is that anisotropies grow rapidly in a contracting universe and will in fact typically come to dominate the dynamics. One solution to this problem is that a matter field with a very stiff equation of state can generate an era of ekpyrosis following matter-domination, and this will dilute the anistropies [21][22][23] (although it has recently been suggested that an ekpyrotic phase may be required also before the phase of matter-domination [24]). Again, the main qualitative predictions of the matter bounce scenario are independent of the details of the ekpyrotic period.…”
Section: Introductionmentioning
confidence: 99%
“…that anisotropy is a natural attractor in contracting cosmologies, and in order to avoid it an enormous fine-tuning of initial conditions has to be invoked, e.g. [37]. The analog of this in the proposed model would be the extreme variation over time of θ around the turnaround point.…”
Section: Evolution Of the Cosmological Backgroundmentioning
confidence: 99%
“…Resolving the BKL instability with an Ekpyrotic phase of contraction after a matter-dominated contracting phase also introduces a fine-tuning problem. As explained in [24], in order to generate N e-folds of matter contraction with sub-dominant anisotropies, one needs the initial ratio of the energy density in anisotropies to that in matter to be smaller than e −6N , which can be an extremely small number. With our massive gravity theory, we showed that the energy densities in anisotropies and matter grow at the same rate, so their ratio remains constant.…”
Section: A Evolution Of Anisotropiesmentioning
confidence: 99%